The Fox and The Dragon : Proyek Kereta Cepat (HSR) Laos Sebagai Strategi â€œBandwagoning for Profitâ€ - Ammar, Faishal; Rosyidin, Mohamad (Journal of International Relations, 2019)
In 2013, China announces a mega project called Belt and Road Initiatives (BRI). This megaproject contain an investment up to US$ 1,6 trillion, in a bid to increase connectivity betweenAsia, Europe, and Africa. This research aims to review one of BRI projects in Laos, which isHSR (High Speed Rail). The HSR run between Kunming and Vientiane, with investment up toUS$ 6 billion. Many views that this project is nothing but a waste and unnecessary. Theburden of debt that Laos had from this project alarmed several entities, such as the WorldBank, and Asian Development Bank. For this project, Laos must contribute in a staggeringamount of US$715 million, many were acquired with loans from China. It is not mentioned ifLaos can’t repay the debt. Nowadays, China is Laos’s biggest trading partner. In thepresence of a rail connection, it is possible that Laos fall into economic dependency withChina. This research aims to prove Laos using bandwagoning as a strategy to gain economicbenefits. This is a qualitative research, with congruent method. The hyphotesis of thisresearch is Laos doing bandwagoning for economic gain. Laos is considered as Jackals inSchweller’s category. Laos take such big risk to increase what it achieved, a big economicgrowth. The result of this research is the hyphotesis is not fully true, as Laos considered asFox, not Jackals.